Artistic practices in the Era of Digitalization: Analysis of the Experience of Modern Art Studios - Donskova, Kateryna; Kutyrоva , Vira (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2025)
The article provides a comprehensive analysis of the transformations of modern artistic practices under the influence of digitalization as a determining factor of socio-cultural changes. It is substantiated that the digital revolution caused a shift from the priority of the material artistic object to processuality, network interaction and participation, as a result of which art appears as a dynamic communicative system. It is emphasized that the theoretical framework of the study was formed on the basis of the theory of social fields and capitals of Pierre Bourdieu and the theory of art of Ron Ayerman, which made it possible to reveal the mechanisms of redistribution of the symbolic status of the artist in the digital environment, as well as with the application of the work of modern Ukrainian researchers in this field. The specifics of digital and post-digital art, which are characterized by openness, interactivity, hybridity of physical and virtual space, temporality, and multiplicity of forms of representation, are analyzed. It is emphasized that the growing role of multisensory experience, physicality and affective involvement of the audience forms new models of perception and evaluation of artistic practices. It is emphasized that digital technologies expand the possibilities of creative self-realization, democratize access to cultural production and create prerequisites for artistic activism, but actualize the risks of devaluation of professional criteria, blurring of authorship and lead to a decrease in expertise.It is noted that the empirical basis of the research is expert interviews with artists and art historians, who have testified an ambivalent attitude towards the use of digital tools in art and art education: they are recognized as a powerful resource for communication and popularization of art, but are not considered as a full-fledged alternative to academic education and direct "master-student" interaction. The conclusions emphasize that contemporary art is increasingly marked by the intensity of social connections, temporality and network logic of cultural production. Digitalization appears not only as a tool, but also as an environment for the formation of new cultural strategies that require further theoretical and empirical understanding.